2015
DOI: 10.1038/gt.2015.35
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical safety and tolerability of a repeatedly administered human leishmaniasis DNA vaccine

Abstract: The leishmaniases are a complex of vector-borne diseases caused by protozoan parasites of the genus Leishmania. LEISHDNAVAX is a multi-antigen, T-cell epitope-enriched DNA vaccine candidate against human leishmaniasis. The vaccine candidate has been proven immunogenic and showed prophylactic efficacy in preclinical studies. Here, we describe the safety testing of LEISHDNAVAX in naive mice and rats, complemented by the demonstration of tolerability in Leishmania-infected mice. Biodistribution and persistence we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
2
18
0
2
Order By: Relevance
“…Lack of efficacy with administration as monotherapy was also observed in repeated-dose studies, which demonstrated good tolerability of LEISHDNAVAX in L. donovani-infected mice (19). Infection inocula and parasite burdens at the end of treatment were similar in this study and the tolerability study (19). Combined treatment approaches are an increasingly attractive treatment option for VL and aim to increase efficacy and to reduce treatment durations and the risk of the emergence of drug resistance (9,20,21).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Lack of efficacy with administration as monotherapy was also observed in repeated-dose studies, which demonstrated good tolerability of LEISHDNAVAX in L. donovani-infected mice (19). Infection inocula and parasite burdens at the end of treatment were similar in this study and the tolerability study (19). Combined treatment approaches are an increasingly attractive treatment option for VL and aim to increase efficacy and to reduce treatment durations and the risk of the emergence of drug resistance (9,20,21).…”
supporting
confidence: 61%
“…LEISHDNAVAX did not show significant antileishmanial efficacy when administered as monotherapy at the highest dose used in prophylactic studies (7); it demonstrated efficacy only when coadministered with liposomal amphotericin B. Lack of efficacy with administration as monotherapy was also observed in repeated-dose studies, which demonstrated good tolerability of LEISHDNAVAX in L. donovani-infected mice (19). Infection inocula and parasite burdens at the end of treatment were similar in this study and the tolerability study (19).…”
mentioning
confidence: 51%
“…The efficacy was further supported by a surge in IFN‐γ and TNF‐α levels along with extreme down‐regulation of IL‐4 and IL‐10 levels . Further, this novel DNA vaccine candidate against leishmaniasis was reported to be safe and well tolerated in both naive‐ and Leishmania‐ infected mice . It can further be evaluated for human clinical trials.…”
Section: Dna Vaccine Candidates In Visceral Leishmaniasismentioning
confidence: 99%
“…Технология мини-кольцевых ДНК активно используется в разработке новых методов лечения неинфекционных заболеваний, но для профилактики инфекционных заболеваний не получила широкого развития. В настоящее время ведется разработка только одной перспективной вакцины для профилактики и лечения лейшманиоза -LEISHDNAVAX [18].…”
Section: мини-кольцевые днкunclassified
“…Следовательно, возможно использование данных ранее проведенных исследований. В случае изменения вектора, системы доставки, способа введения или любых других модификаций, влияющих на поглощение клеткой и/или биораспределение, необходимо проводить новые исследования 18 .…”
Section: особенности проведения доклинических исследованийunclassified